Bridge-Enhanced Anterior Cruciate Ligament Repair: Two-Year Results of a First-in-Human Study. Issue 3 (21st March 2019) - Murray, Martha M.; Kalish, Leslie A.; Fleming, Braden C.; ,; Flutie, Brett; Freiberger, Christina; Henderson, Rachael N.; Perrone, Gabriel S.; Thurber, Laura G.; Proffen, Benedikt L.; Ecklund, Kirsten; Kramer, Dennis E.; et al.
Background: Bridge-enhanced anterior cruciate ligament repair (BEAR) combines suture repair of the anterior cruciate ligament (ACL) with a specific extracellular matrix scaffold (the BEAR scaffold) that is placed in the gap between the torn ends of the ACL to facilitate ligament healing. Purpose/Hypothesis: The purpose of this study was to report the 12- and 24-month outcomes of patients who underwent the BEAR procedure compared with a nonrandomized concurrent control group who underwent ACL reconstruction (ACLR) with an autograft. We hypothesized that the BEAR group would have physical examination findings, patient-reported outcomes, and adverse events that were similar to those of the ACLR group. Study Design: Cohort study; Level of evidence, 2. Methods: Ten patients underwent BEAR, and 10 underwent ACLR with a 4-stranded hamstring autograft. At 24 months, 9 of the 10 BEAR patients and 7 of the 10 ACLR patients completed a study visit. Outcomes reported included International Knee Documentation Committee (IKDC) subjective and objective results, knee anteroposterior (AP) laxity findings via an arthrometer, and functional outcomes. Results: There were no graft or repair failures in the first 24 months after surgery. The IKDC subjective scores in both groups improved significantly from baseline ( P < .0001) at 12 and 24 months, to 84.6 ± 17.2 in the ACLR group and to 91.7 ± 11.7 in the BEAR group. An IKDC objective grade of A (normal) was found in 44% of patients in the BEAR group and in 29% of patients in the ACLR group at 24 months; no patients in either group had C (abnormal) or D (severely abnormal) grades. Arthrometer testing demonstrated mean side-to-side differences in AP laxity that were similar in the 2 groups at 24 months (BEAR, 1.94 ± 2.08 mm; ACLR, 3.14 ± 2.66 mm). Functional hop testing results were similar in the 2 groups at 12 and 24 months after surgery. Hamstring strength indices were significantly higher in the BEAR group compared with the ACLR group ( P = .0001). Conclusion: In this small, first-in-human study, BEAR produced similar outcomes to ACLR with a hamstring autograft. BEAR may result in knee stability and patient-reported outcomes at 2 years sufficient to warrant longer term studies of efficacy in larger groups of patients.